Comparison of South Africa's automotive investment scheme to similar trade, export and investment financial assistance regimes (incentives) of Nigeria and Kenya - Cser, Melinda (Department of Commercial Law, 2016)
Comparison of South Africa 's Automotive Investment Scheme to similar trade, export and investment financial assistance (incentives) regimes of Nigeria and Kenya The AIS is a South African government investment incentive offered within South Africa's Automotive Production and Development Program. The intention of the AIS is to grow and develop the automotive sector through investment in the production of new and/or replacement models and components. The overall aim of the research is to analyse whether the manner in which the AIS incentives seek to achieve the above objectives , and the objectives themselves are aligned and furthermore to indicate the potential weakness of the AIS . The analysis of the weaknesses focuses in particular on potential inconsistencies amongst the provisions of the AIS or amongst the provisions of the AIS and the provisions of its sub - components. Furthermore, the research will review whether the economic benefit criteria of the AIS to be fulfilled by applicants are sufficiently detailed or the lack of details creates uncertainty with the interpretation and implementation. Lastly, the paper will review the transparency elements of the AIS. To obtain an answer to this question, the AIS will be analysed and will be compared against the policies and/or legislation of Nigeria and Kenya, where applicable, to determine whether the policies of these two countries could inform the AIS in achieving its objectives. The analysis will be executed in six chapters. The first chapter is an introduction. Chapter two will cover the policy reasons for the introduction of automotive (and manufacturing related) policies in South Africa, Nigeria and Kenya. Chapter three will provide an overview of the policies and, where applicable, the relevant legislation in the three countries that deal with the automotive industries. As the policies of the three countries are very differently construed , the intention of this paper is not to undertake a full and comprehensive overview of all the relevant South African legislation dealing with tax, customs duties or investment protection to investors in the automotive sector because such legislation is currently one of the key pillars of the Nigerian and Kenyan policies . Therefore, the focus will be on comparing the structure, objectives and operation of the policies of Nigeria and Kenya where it is comparable with the AIS or the APDP. The fourth chapter will deal with the investment specific incentives and benefits provided in the three countries , in particular in relation to cash grants and t heir availability (or not) for investors in Nigeria and Kenya. In relation to Nigeria and Kenya the legislation and policies having similar objectives or structure will be discussed. For South Africa the achievements of the AIS will also be analysed briefly to understand how it has performed against its objectives up until 2015. Chapter five will discuss the institutions and government agencies which are authorized and responsible for handling funding applications, for negotiating funding/investment agreements , and approving and monitoring investment projects related to the automotive industry. The final chapter shall conclude on the findings, and highlight the potential weaknesses of the AIS by providing proposals for improvement based on the lessons learnt from Kenya and/or Nigeria, where or if possible.